Detection of Quorum Sensing System (Cell to Cell Communication) Using Marker Strains in Vibrio alginolyticus Strains and Determine Virulence under Master of this System - Filik, N; Kubilay, A (Journal of the Hellenic Veterinary Medical Society, 2023)
ABSTRACT There are intercellular communication and social behaviors, including Quorum Sensing System (QS) in bacteria. The present study aims to investigate the production of QS signal molecules (N-acyl homoserine lactones, AHLs) in bacterial fish pathogen Vibrio alginolyticus (3 strains) and also determine the virulence using these AHLs under the management of the QS in V. alginolyticus. QS of V. alginolyticus was proved by cross validation assay used by AHL marker bacteria strains (Agrobacterium tumefaciens NT1 and Chromobacterium violaceum CV026). V. alginolyticus was not produced N-butanoyl homoserine lactone (BHL), while N-(3-okzododekanoyl)-L-homoserine lactone (OdDHL) production was detected in V. alginolyticus. The presence of virulence factors, such as biofilm, pigment, rhamnolipid, hemolysis, elastase, protease and amylase production, was investigated as phenotypically in V. alginolyticus. V. alginolyticus was found to produce biofilm, pigment, amylase and elastase; however, it was not determined to produce rhamnolipid, hemolysis and protease virulence.